An American Portfolio: The Ethnic Potpourri (Ethnic Groups in America) - Saunders, Mary Anne P. (Arlington MetaTech Corporation)
This book describes the main processes in the USA, connected with immigration, amecarization and how to become a real member of the USA, what are the main laws people must obey.
Keywords: English Practice